-2a+8+6a=9a-3a

Simple and best practice solution for -2a+8+6a=9a-3a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2a+8+6a=9a-3a equation:


Simplifying
-2a + 8 + 6a = 9a + -3a

Reorder the terms:
8 + -2a + 6a = 9a + -3a

Combine like terms: -2a + 6a = 4a
8 + 4a = 9a + -3a

Combine like terms: 9a + -3a = 6a
8 + 4a = 6a

Solving
8 + 4a = 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
8 + 4a + -6a = 6a + -6a

Combine like terms: 4a + -6a = -2a
8 + -2a = 6a + -6a

Combine like terms: 6a + -6a = 0
8 + -2a = 0

Add '-8' to each side of the equation.
8 + -8 + -2a = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -2a = 0 + -8
-2a = 0 + -8

Combine like terms: 0 + -8 = -8
-2a = -8

Divide each side by '-2'.
a = 4

Simplifying
a = 4

See similar equations:

| 5a=-2 | | 18x^3-27x= | | 52+5y-21=17y-14-3y | | 3x+4/2x+3=x+14/x+8 | | 20=-6a | | x+3/x+1=x-3/x-8 | | -7r=6 | | 4z-15-z+3=0 | | 62-5x=10x+18 | | -6x=9 | | 4d=8-4d | | 4r=-4 | | 9/x+5=15/x+3 | | -(5a+8)+2(a+7)=-4a-5a | | (5x+1)3=15x+3 | | 6x+8/x-2=8 | | m,7-25=-19 | | 3i+3=10-4i | | 4x+4/2=6 | | 2a^2+12a=0 | | 4x+59=10+11 | | 4f=12 | | 20=5a | | 5x(5x-7)(9x+5)=0 | | 3x-9/3=8 | | -8=2b | | -33=-11t | | 4=-2u | | -5+1/2x=-4 | | 66=11w | | -12y=-48 | | (3u-7)(2-u)=0 |

Equations solver categories